1999
DOI: 10.1016/s0896-6273(01)80031-3
|View full text |Cite
|
Sign up to set email alerts
|

GFRα3, a Component of the Artemin Receptor, Is Required for Migration and Survival of the Superior Cervical Ganglion

Abstract: GFR alpha3 is a component of the receptor for the neurotrophic factor artemin. The role of GFR alpha3 in nervous system development was examined by generating mice in which the Gfr alpha3 gene was disrupted. The Gfr alpha3-/- mice exhibited severe defects in the superior cervical ganglion (SCG), whereas other ganglia appeared normal. SCG precursor cells in the mutant embryos failed to migrate to the correct position, and they subsequently failed to innervate the target organs. In wild-type embryos, Gfr alpha3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 46 publications
6
110
0
1
Order By: Relevance
“…To our knowledge, this study is the first rigorous report of nociception in mice lacking GFRα3, and our results are consistent with prior studies that found no discernable phenotype in peripheral sensory ganglia in both artemin and GFRα3-null mice (17,18). The lack of any salient somatosensory abnormalities in naïve Gfrα3 −/− mice suggests that the receptor has no substantial role in sensory nervous system development, despite the fact that it is expressed in ∼20% of adult DRG neurons.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, this study is the first rigorous report of nociception in mice lacking GFRα3, and our results are consistent with prior studies that found no discernable phenotype in peripheral sensory ganglia in both artemin and GFRα3-null mice (17,18). The lack of any salient somatosensory abnormalities in naïve Gfrα3 −/− mice suggests that the receptor has no substantial role in sensory nervous system development, despite the fact that it is expressed in ∼20% of adult DRG neurons.…”
Section: Discussionsupporting
confidence: 91%
“…S5 E and F) were similar between genotypes. These results show that the development of DRG neurons is not influenced by GFRα3 signaling, results consistent with prior analyses of these mice as well as those lacking artemin expression (17,18).…”
Section: Significancesupporting
confidence: 91%
See 1 more Smart Citation
“…corresponding phenotypes of ligand and/or receptor mouse knockouts (31,32). In summary, GDNF, NTN, EVN/ART, and PSP are part of a neurotrophic signaling system whereby specific high affinity ligand-binding subunits (GFR␣-1 to GFR␣-4) can interact with the same tyrosine kinase subunit (cRET) to elicit functional responses in neuronal cells.…”
Section: /Ebi Data Bank With Accession Number(s) Aj294475 (For Rat Gfmentioning
confidence: 99%
“…However, examination of fixed embryos has shown that the superior cervical ganglion forms from cells that first migrate ventrally to form a column of cells that is continuous with the stellate ganglion primordium at lower cervical levels; some cells subsequently migrate rostrally to form the superior cervical ganglion (Rubin, 1985). This rostral migration occurs between E12.5 and E14.5 in mice (Nishino et al, 1999;Enomoto et al, 2001). It would be interesting to examine the phenotype and the mode of migration of the cells that migrate rostrally to form the superior cervical ganglion.…”
Section: Differentiation and Cell Migrationmentioning
confidence: 99%